Immune checkpoint inhibitor induced nephrotoxicity: An ongoing challenge - Catalano, Martina; Roviello, Giandomenico; Galli, Ilaria Camilla; Santi, Raffaella; Nesi, Gabriella (Frontiers in Medicine, 2022)
Although immune checkpoint inhibitors (ICIs) have dramatically revolutionized the field of oncology over the last decade, severe immune-related adverse events (irAEs) are potentially life-threatening. In comparison with toxicities involving the skin, gastrointestinal tract and endocrine system, nephrotoxicity is less common but often underestimated due to difficult diagnosis. Management usually consists of treatment discontinuation and/or corticosteroid use. In this review, we summarize current knowledge of ICI-induced nephrotoxicity, evaluating drawbacks and future perspectives.